Validity and reliability testing of the Shatri Sinulingga psychosomatic test (SSPT) questionnaire as a screening instrument for psychosomatic disorders in Indonesia - Shatri, Hamzah; Sinulingga, Dika I.; Faisal, Edward; Irvianita, Vinandia; Putranto, Rudi; Ardani, Yanuar; Erlita, Diana; Jeger, Dian P.; Browijoyo, Isa A. (Narra J, 2024)
The incidence of psychosomatic disorders is increasing in Indonesia, and therefore screening instruments that are culturally appropriate for the Indonesian population are needed. The aim of this study was to assess the validity and reliability of the Shatri Sinulingga psychosomatic test (SSPT) questionnaire as a screening instrument for psychosomatic disorders in Indonesia. An analytic descriptive cross-sectional study divided into two stages (questionnaire formulation and distribution through the Psikosom.id application) was conducted in 2023. The validity test was carried out using the product moment technique, and Cronbach's alpha assessment was carried out to evaluate the reliability of the questionnaire. A total of 372 participants were included, with a mean age of 39.24 years old. The SSPT questionnaire scores had strong correlations with the scores of hospital anxiety and depression scale (HADS) (r=0.668; p<0.001) and the Symptom Checklist-90 (SCL-90) (r=0.674; p<0.001); and moderately correlated with the score of fatigue severity scale (FSS) (r=0.505; p<0.001) and Pittsburgh Sleep Quality Index (PSQI) (r=0.492; p<0.001). The correlation coefficient (r) value of each SSPT question ranged from 0.389–0.726, and all r higher than r table with an overall Cronbach’s alpha of 0.744. The SSPT questionnaire's strong predictive performance: had a sensitivity of 75.6% and specificity of 71.4% with an area under the curve (AUC) of 81% (95%CI: 76.6–85.4%; p<0.001) to HADS; sensitivity of 80% and specificity of 58.6% with an AUC of 75.1% (95%CI: 70–80.2%; p<0.001) to FSS; sensitivity of 64% and specificity of 67.5% with an AUC of 71.2% (95%CI:  65.4–77%; p<0.001) to PSQI; and had sensitivity of 78% and specificity of 67.4% with an AUC of 80.9% (95%CI:  76.6–85.3%; p<0.001) to SCL-90. The study highlights that the SSPT questionnaire is valid and reliable to be used as a screening instrument for psychosomatic disorders in Indonesia.